The influence of blended in-service teacher professional training on EFL teacher creativity and teaching effectiveness - Arifani, Yudhi; Mohd. Khaja, Farah Natchiar; Sri Suryanti,; Wardhono, Agus (Penerbit Universiti Kebangsaan Malaysia, 2019)
Current seminal studies on teacher creativity and teaching effectiveness have been widely investigated by numerous researchers. Most of them explored both variables (teacher creativity and effectiveness) from various aspects such as the perspectives of teachers, learners, and of gender but they failed to address one important variable, namely the influence of professional development background on these variables. Consequently, this study aims to analyse the influence of blended teacher professional training on teaching creativity and teaching effectiveness from the learners’ perspective. A sample of 901 learners from various secondary schools in East Java province was randomly assigned to rate 120 EFL teachers using both the English language teaching creativity scale (ELT-CS) and the English language teaching effectiveness scale (ELT-ES). For this purpose, a validated and reliable five-point Likert scale of ELT-CS and ELT-ES (1 = totally disagree, 2 = disagree, 3 = partially agree, 4 = agree and 5 = totally agree) has been employed. After administering the questionnaires, the data were analysed using structural equation modelling (SEM). The findings indicate a positive influence of blended professional training on EFL teachers' creativity and their teaching effectiveness. As for the indicators of teaching effectiveness and creativity, knowledge, subject matter, independent learning, learning environment, and material variables show the strongest influences. Conversely, fluency, flexibility, originality, and elaboration variables show the weakest influences. The detailed influences of each indicator from both variables were also elaborated on. Finally, recommendations for further research are presented.